Perspectives on Tannins - Szczurek, Andrzej (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Tannins are a family of versatile, natural phenolic biomolecules whose key role is to protect plants against insects and fungi. They are also valuable in use for humans. We show tannins' antioxidant and antibacterial properties, in addition to their potential application in the food industry. We prove the accessibility of condensed tannins to a wide range of potential applications, including NH3 neutralizer, the building block of numerous porous materials, such as foams, organic, and carbon gels. Finally, they are known as wood adhesives, heavy metal scavengers, and corrosion inhibitors. With this book, we want to present the most promising perspectives of tannin.